PENGEMBANGAN BAHAN AJAR DIGITAL MENGGUNAKAN CANVA PADA SUBTEMA LINGKUNGAN TEMPAT TINGGALKU - Yulia Fauziah; Griet Helena Laihad; Mira Mirawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to develop digital teaching materials using Canva on the subtheme of my living environment in class IV SD Negeri Ciapus 02. The method in this study uses the Research and Development method with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). This research involved one media and language expert lecturer each, and one material expert teacher. The population and sample of this study were fourth grade students at SD Negeri Ciapus 02 Bogor Regency in the academic year 2022/2023 with a total of 28 students. The instruments used in this study consisted of expert validation sheets and student questionnaire sheets. Based on the average results carried out by validators, the average media expert is 96%, the average language expert is 97.3%, and the material expert is 98.6%. And based on the trial conducted on students obtained a result of 89.9% in the "Very Good" category. So it can be concluded that digital teaching materials using Canva on the subtheme of my living environment are feasible and effective for use in learning in elementary schools.